Determinants Affecting Dividend Policy: A Study on A Sample of Companies Listed on the Iraq Stock Exchange - Khalid Khider (Indonesian Journal Publisher, 2026)
The study aimed to diagnose and examine the main determinants of the dividend policy, while providing an integrated comprehensive picture of the intellectual and theoretical frameworks that framed the mechanisms of direct and indirect influence that can be exercised by those determinants, which varied between financial, economic, political and institutional variables in the interpretation of dividend payments, complemented by an empirical quantitative analysis in which the Generalized Method of Moment (GMM) based on balanced double data was employedPanel Data Balance for a number of business companies listed on the financial markets of the Republic of Iraq, for the period (2010-2020). The study found the diversity of the determinants of dividend policies in terms of profitability, liquidity, growth, and leverage, as well as the variation of their impact from one model of dividend policy to another. On the other hand, the study confirmed the unification of the trend of impact in terms of being positive for the variable of profitability, liquidity and growth versus the negative impact of the leverage variable in dividend policies In the sample companies of the study.